Peg-interferon plus ribavirin in chronic hepatitis C: cost-efficacy and pharmacoutilization in clinical practice - Cavalletto, Luisa; Bernardinello, Elisabetta; Diodati, Giulio; Raise, Enzo; Gatta, Angelo; Chemello, Liliana (Farmeconomia. Health Economics and Therapeutic Pathways, 2008)
The current standard of care for the treatment of chronic hepatitis C virus (HCV) infection is combination therapy with Peg-interferon (IFN) alpha-2a or alpha-2b type plus ribavirin (RBV). This antiviral schedule can in fact avoid the three fold mortality rates associated to untreated cases with HCV infection, by inducing viral eradication and liver damage regression, so as to define the patients “definitively cured” from liver disease. This analysis describes the modalities of antiviral treatment in the Veneto region, in particular the therapy-schedule mainly used and compares the cost-effectiveness of treatment with the 2 available Peg-IFNs with strategies proposed as in the every day practice. Twelve on line hepatologic units, centralized by a network program on “Surveillance and Control of HCV Infection in the Veneto Region”, prospectively collected data and, of these, we evaluated 450 subjects that underwent antiviral therapy for chronic hepatitis or cirrhosis. A post hoc retrospective analysis of cases treated from January 2003 to December 2005 was performed, grouping the study population in 166 cases treated with Peg-IFN alpha-2a (Pegasys®, Roche, fixed-dose of 180 μg/weekly) and 284 that received Peg-IFN alpha-2b (Peg-Intron®, Schering-Plough, weight-adjusted-dose from 50 to 150 μg/weekly), both in combination therapy with ribavirin (Copegus®, Roche, or Rebetol®, Schering-Plough, weight-adjusted-dose of 15 mg/kg/daily). Epidemiological characteristics and cumulative rate of end-of-therapy response and Sustained Virological Response (SVR) were similar in the 2 groups, but 78% of cases treated with Peg-IFN alpha-2b and RBV received a significantly lower dose with respect to the weight-adjusted dose. This event conditioned efficacy to therapy as demonstrated in cases that received a < 1 μg/kg dose with respect to those treated with > 1 μg/kg (respectively SVR: 49% vs 66%, p < 0,01), particularly in genotype HCV-1 (SVR: 29% vs 51%, p = 0,01), known to be more resistant to IFN-therapy. The overall cost of antiviral therapy in this study population was about € 3,528,000/450 treated cases and considering the 269 that reached SVR (98 and 171, respectively by Peg-IFN alpha-2a or 2b and RBV therapy), the cost/SVR was € 15,632 and € 11,672 in the 2 groups. In conclusion, the optimization of Peg-IFN therapy, that is the use of the full dose, particularly in cases treated with a weight-adjusted Peg-IFN alpha-2b and RBV, at the standard of care dosage of 1.5 μg/kg/week and 15 mg/kg/day respectively, will allow a better efficacy, especially in genotype HCV-1 with an increase of 11% in SVR (43% to 54%) at a lower cost.